Neural Efficiency and Acquired Motor Skills: An fMRI Study of Expert Athletes - Zhang, Lanlan; Qiu, Fanghui; Zhu, Hua; Xiang, Mingqiang; Zhou, Liangjun (Frontiers in Psychology, 2019)
The neural efficiency hypothesis was investigated. Functional magnetic resonance imaging was used to study differences in brain activity between players imagining performing different movements: basketball players imagined throwing, and volleyball players imagined serving. These comparisons of brain activity among players imagining movements from their self-sport (e.g., a basketball throw in basketball players) versus movements from an other-sport (e.g., a volleyball serve in basketball players) revealed the neural energy consumption each task costs. The results showed better temporal congruence between motor execution and motor imagery and vividness of motor imagery, but lower levels of activation in the left putamen, inferior parietal lobule, supplementary motor area, postcentral gyrus and the right insula when both groups of players imagined movements from their self-sport compared with when they imagined movements from the other-sport. Athletes were more effective in the representation of the motor sequences and the interoception of the motor sequences for their self-sport. The findings of present study suggest that elite athletes achieved superior behavioral performance with minimal neural energy consumption, thus confirming the neural efficiency hypotheses.